Rural Water Supply in Mexico - Silva Rodríguez de San Miguel, Jorge Alejandro (2016)
The supply of water to rural areas has historically provided the Mexican government with a significant challenge. Years of uncertainty in relation to responsibility for water supply, as well as geographical differences across the country and a division between rural and urban areas, explain this phenomenon. I have reviewed in this paper a substantial proportion of the literature on this topic, the reasons behind its nature, and the solutions to the problem in Mexico, as my main aim. The key conclusion is that while improvements in rural water supply in Mexico have been made, further work is required for equality in its supply.